1992
DOI: 10.1029/92gl00577
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal 3He and manganese plumes at 19°29′S on the Central Indian Ridge

Abstract: We report the discovery of a hydrothermal helium‐3 plume north of the Indian Triple Junction, on the Central Indian Ridge at 19°29′S. Water column δ3He anomalies show a spike of 33.8% at 2460 meter depth, i.e. the highest δ3He anomaly recorded so far in the Indian ocean. The helium‐3 data are correlated with manganese, giving a Mn/3He ratio of 700 mol/cm3 (3.8×104 g/cm3STP). The CH4/3He ratio deduced from available CH4/Mn data in the same area is around 7×106. These values are close to what is observed on wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…Corresponding to a water-column hydrothermal signal discovered as early as the late eighties and recently (Jean-Baptiste et al 1992;Kawagucci et al 2008), two new areas of hydrothermal activity with associated chemosynthetic fauna were newly discovered in 2009 on the CIR at 18-20 S (Nakamura et al 2012). The Solitaire hydrothermal field extends over an area measuring approximately 50 Â 50 m, which is comparable to the areas of the KHF and Edmond fields.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Corresponding to a water-column hydrothermal signal discovered as early as the late eighties and recently (Jean-Baptiste et al 1992;Kawagucci et al 2008), two new areas of hydrothermal activity with associated chemosynthetic fauna were newly discovered in 2009 on the CIR at 18-20 S (Nakamura et al 2012). The Solitaire hydrothermal field extends over an area measuring approximately 50 Â 50 m, which is comparable to the areas of the KHF and Edmond fields.…”
Section: Introductionmentioning
confidence: 75%
“…The Solitaire field is located at the western flank of the CIR-S15B segment center. It was first predicted by a hydrothermal plume anomaly surveyed in the late 1980s (Jean-Baptiste et al 1992). As described in Sect.…”
Section: Tectonic Background Of Hydrothermal Fieldsmentioning
confidence: 99%
“…Kumagai et al (2008), 4. Van Dover et al (2001 the area situated from 18-20 S on the CIR had been suggested by two previous surveys that detected hydrothermal anomalies in the water column (Jean-Baptiste et al 1992;German et al 2001). In December 2006, an extensive plume survey was conducted in the CIR region approximately 19 S during the KH 06-4 cruise on the R/V Hakuho-maru using vertical and tow-yo hydrocasts and the AUV r2D4.…”
Section: Dodo Hydrothermal Fieldmentioning
confidence: 99%
“…The location of the Solitaire hydrothermal field is approximately 150 km south of the Dodo hydrothermal field. As for the Dodo field, during the KH 06-4 cruise on the R/V Hakuho-maru in December 2006, an extensive plume survey was conducted using vertical and tow-yo hydrocasts and the AUV r2D4 in the area where the existence of hydrothermal activity had been suggested by previous studies (Jean-Baptiste et al 1992;German et al 2001). During the survey, evident plume signatures of anomalies hydrothermally derived CH 4 , Mn Fig.…”
Section: Solitaire Hydrothermal Fieldmentioning
confidence: 99%
“…They also reported excess δ 3 He of more than 10% at mid-depth (2000 -3000 m) in the central Indian Ocean. Jean-Baptiste et al (1992) and Kawagucci et al (2008) found hydrothermal plumes with δ 3 He higher than 30% in the area of 18 -20°S on the Central Indian Ridge, near the Rodriguez Triple Junction with anomalies of methane isotopes. Moreover, Gamo et al (2001) found high temperature (360°C) fluids near the Rodriguez Triple Junction and reported a very high 3 He/ 4 He ratio of 7.9 R a of the vent fluid, where R a is the atmospheric 3 He/ 4 He ratio of 1.4 × 10 -6 .…”
Section: Introductionmentioning
confidence: 99%